Phenome-wide association analysis of LDL-cholesterol lowering genetic variants in PCSK9 - Schmidt, Amand F; Holmes, Michael V; Preiss, David; Swerdlow, Daniel I; Denaxas, Spiros; Fatemifar, Ghazaleh; Faraway, Rupert; Finan, Chris; Valentine, Dennis; Fairhurst-Hunter, Zammy; Hartwig, Fernando Pires; Horta, Bernardo Lessa; et al. (BMC cardiovascular disorders, 2019)
BACKGROUND: We characterised the phenotypic consequence of genetic variation at the PCSK9 locus and compared findings with recent trials of pharmacological inhibitors of PCSK9. METHODS: Published and individual participant level data (300,000+ participants) were combined to construct a weighted PCSK9 gene-centric score (GS). Seventeen randomized placebo controlled PCSK9 inhibitor trials were included, providing data on 79,578 participants. Results were scaled to a one mmol/L lower LDL-C concentration. RESULTS: The PCSK9 GS (comprising 4 SNPs) associations with plasma lipid and apolipoprotein levels were consistent in direction with treatment effects. The GS odds ratio (OR) for myocardial infarction (MI) was 0.53 (95% CI 0.42; 0.68), compared to a PCSK9 inhibitor effect of 0.90 (95% CI 0.86; 0.93). For ischemic stroke ORs were 0.84 (95% CI 0.57; 1.22) for the GS, compared to 0.85 (95% CI 0.78; 0.93) in the drug trials. ORs with type 2 diabetes mellitus (T2DM) were 1.29 (95% CI 1.11; 1.50) for the GS, as compared to 1.00 (95% CI 0.96; 1.04) for incident T2DM in PCSK9 inhibitor trials. No genetic associations were observed for cancer, heart failure, atrial fibrillation, chronic obstructive pulmonary disease, or Alzheimer's disease - outcomes for which large-scale trial data were unavailable. CONCLUSIONS: Genetic variation at the PCSK9 locus recapitulates the effects of therapeutic inhibition of PCSK9 on major blood lipid fractions and MI. While indicating an increased risk of T2DM, no other possible safety concerns were shown; although precision was moderate.
Keywords: proproteinkonvertasa subtilisin/kexin typu 9; Brain Ischemia; biologické markery; PCSK9 Inhibitors; PCSK9 inhibitory; Risk Assessment; lidé; Dyslipidemias; výsledek terapie; Randomized Controlled Trials as Topic; Risk Factors; Polymorphism, Single Nucleotide; Genetic association studies; LDL-cholesterol; celogenomová asociační studie; Stroke; anticholesteremika; Down-Regulation; Serine Proteinase Inhibitors; hodnocení rizik; jednonukleotidový polymorfismus; infarkt myokardu; down regulace; Humans; Myocardial Infarction; Proprotein Convertase 9; Anticholesteremic Agents; inhibitory serinových proteinas; ischemie mozku; randomizované kontrolované studie jako téma; cévní mozková příhoda; Phenome-wide association scan; Biomarkers; dyslipidemie; Cholesterol, LDL; Treatment Outcome; Genome-Wide Association Study; Mendelian randomisation; rizikové faktory